Improving Customer Loyalty by Getting Rid of the Misunderstanding (Global Journal of Management and Business Research, 2014)
With the aggravation of the market competition, customer loyalty has become one of the most decisive factors that will affect the long-term profits of an enterprise. Misunderstanding of enterprise management in China is probably to be wiped out in our comprehension of customer loyalty only if we can correctly grasp its connotation as well as take effective strategies. And then, we can increase the loyalty of our customers and keep our business invincible in the fierce market competition.
Keywords: customer loyalty; misunderstanding; strategy